In-Depth Duodenal Transcriptome Survey in Chickens with Divergent Feed Efficiency Using RNA-Seq: e0136765 - Yi, Guoqiang; Yuan, Jingwei; Bi, Huijuan; Yan, Wei; Yang, Ning; Qu, Lujiang (PloS one, 2015)
Since the feed cost is a major determinant of profitability in poultry industry, how to improve feed efficiency through genetic selection is an intriguing subject for breeders and producers. As a more suitable indicator assessing feed efficiency, residual feed intake (RFI) is defined as the difference between observed and expected feed intake based on maintenance and growth. However, the genetic mechanisms responsible for RFI in chickens are still less well appreciated. In this study, we investigated the duodenal transcriptome architecture of extreme RFI phenotypes in the six brown-egg dwarf hens (three per group) using RNA sequencing technology. Among all mapped reads, an average of 75.62% fell into annotated exons, 5.50% were located in introns, and the remaining 18.88% were assigned to intergenic regions. In total, we identified 41 promising candidate genes by differential expression analysis between the low and high RFI groups. Furthermore, qRT-PCR assays were designed for 10 randomly chosen genes, and nine (90.00%) were successfully validated. Functional annotation analyses revealed that these significant genes belong to several specific biological functions related to digestibility, metabolism and biosynthesis processes as well as energy homeostasis. We also predicted 253 intergenic coding transcripts, and these transcripts were mainly involved in fundamental biological regulation and metabolism processes. Our findings provided a pioneering exploration of biological basis underlying divergent RFI using RNA-Seq, which pinpoints promising candidate genes of functional relevance, is helpful to guide future breeding strategies to optimize feed efficiency and assists in improving the current gene annotation in chickens.